Online PID controller tuning using tree physiology optimization - Halim, A.H. (Institute of Electrical and Electronics Engineers Inc., 2017)
This paper presents the tuning of Proportional Integral Derivative (PID) controller parameter using a novel Tree Physiology Optimization (TPO). TPO is another variant of metaheuristic optimization that inspired from a plant growth system. In the proposed method, every possible solution denoted as tree-shoots is driven by variables from the root system. The concept is inspired from the propagation of shoot system towards better sunlight. At the same time, the root system receive fitness value which then triggers root extension towards a better possible factor and then supplied to the shoot system. This iterative correlation leads towards optimum solution. A simulation of online PID-tuning is applied to demonstrate the effectiveness of proposed algorithm and compared with other optimization method which are Particle Swarm Optimization (PSO) and Ziegler-Nichols (Z-N) method. © 2016 IEEE.